Multicargo Porous Cochlear Electrode Coating for Antifibrosis After Cochlear Implantation - Lei Ren; Yangnan Hu; Xiaoqiong Ding; Menghui Liao; Tian Shen; Sixing Cao; Hui Zhang; Hong Cheng; Yanru Qi; Pan Feng; Xinyi Pang; Ling Lu; et al. (Advanced Science)
Abstract Severe to profound sensorineural hearing loss seriously affects the communication and cognitive ability of the patients. Cochlear implantation (CI) is currently the most effective treatment, while it may damage the remaining inner ear function due to its poor biocompatibility and the resultant fibrosis. Herein, a porous methacrylated poly(dimethylsiloxane) (MA‐PDMS)‐coated cochlear electrode is presented for CI and hearing protection. The porous MA‐PDMS is filled with a hybrid hydrogel system made of dexamethasone sodium phosphate (Dex), Ti3C2Tx MXene (MXene), and methacrylate gelatin (GelMA). The coating shows good biocompatibility and drug loading and release capacity in vitro, protective effects on hair cells (HCs) and spiral ganglion neurons (SGNs) of the inner ear, as well as the residual hearing protection and the effective fibrosis reduction in vivo. It is anticipated that this porous electrode drug‐loading coating may provide a valuable reference strategy for the future cochlear electrode transplantation system.